2021
DOI: 10.3390/su132112014
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Level of Information about Sustainability of Edible Insects in a Traditionally Non-Insect-Eating Country: Exploratory Study

Abstract: Insects have been reported as a possible alternative solution to help feed the growing world population with less stress on the planet, thus contributing to the preservation of the environment and natural ecosystems. However, the consumption of edible insects (EIs), although culturally accepted for some communities, is not readily accepted for others. Hence this work explores the level of information that people in a traditionally non-insect-eating country have about the sustainability issues related with EIs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Sousa [55] reported low adherence to MD in Portugal, with a high impact on cardiovascular diseases. Although edible insects are not a traditional food in Portugal, studies have demonstrated that people are to some extent prone to start consuming products that contain edible insects as a complement to their diet, mostly motivated by their sustainability aspects [8,20]. This confirms that people are aligned with the need to promote more sustainable food supply chains in order to meet the goals established under the SDG of the UN.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Sousa [55] reported low adherence to MD in Portugal, with a high impact on cardiovascular diseases. Although edible insects are not a traditional food in Portugal, studies have demonstrated that people are to some extent prone to start consuming products that contain edible insects as a complement to their diet, mostly motivated by their sustainability aspects [8,20]. This confirms that people are aligned with the need to promote more sustainable food supply chains in order to meet the goals established under the SDG of the UN.…”
Section: Discussionmentioning
confidence: 82%
“…It has been estimated that the regular consumption of insects has been part of the traditional diets of over two billion people worldwide [7]. Insects have been identified as a more sustainable alternative when compared with other, more conventional animal protein sources [6,[8][9][10]. In this way, they can contribute to greatly relieving the pressure on the planet and on ecosystems given the imminent need to feed the world population, which is constantly growing.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the above, it is also important to verify consumers’ knowledge. For example, the study by Guine et al [ 84 ] shows that although the knowledge about the sustainability and consumption of insects in some countries is quite common, many consumers still rely on misconceptions. Therefore, this is significantly dependent on the national educational strategies which would be based on such direct motivational techniques as encouraging tasting.…”
Section: Discussionmentioning
confidence: 99%
“…Although eating insects is considered normal in many areas of the globe where this practice is culturally accepted and valued, it is also true that in other regions of the world, people have developed a solid reluctance to entomophagy [ 44 , 45 ]. Over two billion people worldwide consume insects regularly as part of their traditional diets [ 46 ].…”
Section: Processing and Usesmentioning
confidence: 99%